Setup and results of pyramidal microwave absorbers using rice husks - Nornikman, Hassan; Fareq, Malek, Dr.; Ahmed, M.; Wee, Fwen Hoon; Soh, Ping Jack; Azremi, Abdullah Al Hadi, Dr.; Ghani, S. A.; Hasnain, A.; Taib, M. N. (EMW Publishing, 2011)
Link to publisher's homepage at http://emacademy.org/emwave/